1997
DOI: 10.1007/s000180050115
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional characterization of recombinant von Willebrand factor produced on a large scale

Abstract: Recombinant von Willebrand factor (r-vWF) was produced in serum-free medium on a large scale in recombinant Chinese hamster ovary cells and was purified from fermentation supernatant by a combination of anion exchange chromatography and heparin affinity chromatography. Heparin affinity chromatography yielded r-vWF polymers of different degrees of multimerization. r-vWF was analysed by qualitative and quantitative functional analysis. We could show that while binding of r-vWF to platelets did not depend on mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Recombinant vWf was a kind gift from Professor F. Dorner, Vienna, Austria. Recombinant vWf has been shown to mediate platelet aggregation and to promote binding of collagen and coagulation factor VIII with activity comparable to human-plasma-derived vWf (Fischer et al, 1997). Goat anti-vWf antibodies were purchased from Kordia ; antibodies against recombinant vWbp (see below) developed in chicken were obtained from Immunsystem AB ; mouse anti-E-tag antibodies and horseradish peroxidase (HRP)-labelled anti-mouse antibodies were from Amersham Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant vWf was a kind gift from Professor F. Dorner, Vienna, Austria. Recombinant vWf has been shown to mediate platelet aggregation and to promote binding of collagen and coagulation factor VIII with activity comparable to human-plasma-derived vWf (Fischer et al, 1997). Goat anti-vWf antibodies were purchased from Kordia ; antibodies against recombinant vWbp (see below) developed in chicken were obtained from Immunsystem AB ; mouse anti-E-tag antibodies and horseradish peroxidase (HRP)-labelled anti-mouse antibodies were from Amersham Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…1d) Biological functions VWF performs a large number of functions in the human body [14][15][16]71]; binding to factor VIII and platelet surface glycoprotein is prominent among them [6,72,73]. The binding of VWF to platelets is regulated by its initial interaction with connective tissue and also by shear stress in flowing blood.…”
Section: Domain A3mentioning
confidence: 99%
“…rvWF is composed of mature subunits [13]. Fischer et al showed that rvWF produced on a large scale under serum-free culture conditions exhibits all the qualitative and quantitative functional properties which allow it to mediate platelet aggregation, promote collagen binding and binding of coagulation factor VIII with activity comparable to human plasma-derived vWF [14]. Herrmann et al also observed similar adhesion promotion for S. aureus when recombinant vWF was used [12].…”
Section: Introductionmentioning
confidence: 99%